(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This article deals with the main aspects of geological and geomorphological hazards (geohazards) assessment by presenting review of GIS-based methodology for identification and analysis of environmental hazards of such type to which the Daugavpils and Ilūkste districts are exposed. It includes (1) critical review of the availability and state of the art in data sources about geological risk factors, (2) a description of using geomatics methods for obtaining thematic layers of risk factors and techniques of their combining and overlaying, and (3) an analysis and assessment of summary geohazard risk. Such a complex GIS-based studying of geohazards has not been performed before in the territory under study, nor has it been attempted in Latvia. At the same time obtained results allow highlighting areas exposed to geological risk within the Daugavpils and Ilūkste districts, hence providing relevant information for spatial planning of these territories.